Corruption and Development: The Need of International Investigations with a Multijurisdictional Approach and the Involvement of Multilateral Development Banks with National Authorities - Osorio Rincon, Andrea (2016)
The authors argue that while both Multilateral Development Banks (MDBs) and national governments have mechanisms to fight corruption, the outcomes of these enforcement mechanisms diverge. MDBs are interested in the causes and effects of corruption from a development perspective and, as such, tend to sanction Small and Medium Enterprises and individuals, while national governments are focused on a more punitive outcome, targeting larger multinational corporations. The article examines the enforcement objectives articulated in national legislation, namely the American Foreign and Corrupt Practices Act and its Canadian counterpart (the CFPOA) as well as several Canadian cases, on the one hand, and the tools and outcomes of the MDBs’ Sanctions Systems on the other. The authors conclude that national enforcement efforts and MDBs’ sanctions outcomes intersect in their fight against international corruption in that their results are complimentary; the former punishing large-scale offenders, while the latter ensuring the integrity of development projects